The Practice of Moderate Education to Prevent Interreligious Conflict - Bayan Okenova; Wenxin Xu; Samiullah Adel (International Islamic Studies Development and Research Center (IISDRC), 2025)
The issue of religious moderation is back in the discussion of state elites, academics, religious leaders and the public today, because religious conflicts can trigger community divisions and even the collapse of a nation. In fact, the religious moderation movement is one of the solutions to prevent religious conflicts in the midst of society. Many ways can be done to educate the public about the importance of living in harmony, peace and mutual respect despite different beliefs. Among them is through social community activities. In fact, the prevention of inter-religious conflict based on social community activities has offered a new method for the progress of living together in pluralism. This research aims to see, analyze and describe how the model of inter-religious conflict prevention based on social community activities in West Sumatra Province. The research was conducted using a qualitative approach (multi case single-site exploratory case study). Data were collected through in-depth interviews with twenty-five informants categorized as religious leaders, community leaders, traditional leaders, administrators of the Religious Harmony Forum (FKUB), university academics and government officials who take regional policies. All informants are Muslims, Catholics, Protestants, Hindus and Buddhists who were selected using the purposive sampling technique. As supporting data, the author also analyzed literature sourced from various books, religious scriptures, and scientific articles related to this research. Overall, the research findings found four models of inter-religious conflict prevention based on community activities in West Sumatra Province. The four models are: i) establishing a dialog space between religious leaders, ii) community work through social activities, iii) traditional bonds of mutual cooperation, iv) support from community and religious leaders. The results of this research are discussed with various theories and results of previous research, and can be used as one of the references to create peace, harmony, peace, harmony and uphold the principle of togetherness in the midst of pluralistic societies.